2015
DOI: 10.1111/dom.12539
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liraglutide versus placebo added to basal insulin analogues (with or without metformin) in patients with type 2 diabetes: a randomized, placebo‐controlled trial

Abstract: AimTo confirm the superiority, compared with placebo, of adding liraglutide to pre‐existing basal insulin analogue ± metformin in adults with inadequately controlled type 2 diabetes [glycated haemoglobin (HbA1c) 7.0–10.0% (53–86 mmol/mol)].MethodsIn this 26‐week, double‐blind, parallel‐group study, conducted in clinics or hospitals, 451 subjects were randomized 1 : 1 to once‐daily liraglutide 1.8 mg (dose escalated from 0.6 and 1.2 mg/day, respectively, for 1 week each; n = 226) or placebo (n = 225) added to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 46 publications
12
98
1
5
Order By: Relevance
“…Our study supports previous data on liraglutide improvements in glucose control and weight reduction. HbA1c improvement was directly related to basal HbA1c in concordance with previous studies [9][10][11]. As indicated in our study, greater proportion of patients treated with liraglutide reached the target level of HbA1c < 7% than the other two agents, without accompanying an increased risk of hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study supports previous data on liraglutide improvements in glucose control and weight reduction. HbA1c improvement was directly related to basal HbA1c in concordance with previous studies [9][10][11]. As indicated in our study, greater proportion of patients treated with liraglutide reached the target level of HbA1c < 7% than the other two agents, without accompanying an increased risk of hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies indicated that both GLP-1RA and DPP4i have the priority over metformin and sulfonylurea in reducing plasma glucose and body weight, and increasing insulin sensitivity. However, these studies seldom select the newly diagnosed diabetic patients as subjects, and rarely evaluate the adipokines profile [8][9][10][11]. To our knowledge, no studies have addressed the effect of liraglutide and sitagliptin treatment on plasma glycemic control, weight loss and circulating adipokines in newly diagnosed diabetic patients in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that better glucose-lowering effects can be obtained by additional administration of liraglutide in patients with type 2 diabetes on insulin therapy without developing hypoglycemia or weight gain, and that insulin requirements can be reduced [6][7][8][9][10]. It is very interesting that simultaneous and combined use of liraglutide and insulin glargine as the initial treatment in patients with type 2 diabetes under hyperglycemic or so-called glucotoxic conditions resulted in similar effects to those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of confirmed hypoglycaemia was significantly ( P < 0.0001) lower with liraglutide than with insulin aspart, while gastrointestinal AEs occurred more frequently with liraglutide. Another 26‐week study that compared liraglutide with placebo, both added to basal insulin with or without metformin, found that both HbA 1c and body weight decreased significantly ( P < 0.0001) more with liraglutide than with placebo 42. Gastrointestinal AEs were more common with liraglutide relative to placebo, as was confirmed hypoglycaemia ( P = 0.04).…”
Section: Treatment Intensification Of Basal Insulin With Glp‐1rasmentioning
confidence: 99%